The Best Stories and Tales of Leon Tolstoy - Tolstoy, Leo (Indiana Publishing House; London, 2007)
"The Best Stories and Tales of Leo Tolstoy" is a collection of some of the most celebrated works by the renowned Russian author Leo Tolstoy. This anthology features a selection of his short stories and novellas that explore profound themes such as morality, spirituality, human nature, and social justice. Through masterful storytelling, Tolstoy delves into the lives of everyday people as well as aristocrats, offering deep insights into the human condition. The collection includes timeless tales that reflect his philosophical beliefs, making it an essential read for those interested in classic literature and moral introspection.